1987
DOI: 10.1021/j100304a014
|View full text |Cite
|
Sign up to set email alerts
|

Photolytic preparation and isomerization of thionyl imide, thiocyanic acid, thionitrous acid, and nitrogen hydroxide sulfide in an argon matrix: an experimental and theoretical study

Abstract: The molecule HONS in the trans geometry has been produced by selective photolysis from HNSO and several of its isotopes in an argon matrix at 12 K. The new molecule was characterized by its IR spectrum in conjunction with a normal-coordinate analysis and ab initio calculations. With this "missing link" the HNSO transformation scheme is completed which shows that starting from HNSO in a low-temperature matrix, the molecules HOSN, HSNO, and HONS in the cis and/or trans configuration(s) can be produced by selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 0 publications
4
34
0
1
Order By: Relevance
“…However, a key aspect of HSNO's properties that seems to have been overlooked in these discussions is its mobile hydrogen, allowing facile 1,3 hydrogen shift and formation of four isomers with the same chemical equation (13)-a feature described in the seminal studies by Goehring in the 1950s (23) and by Müller and Nonella later on (24,25) that distinguishes HSNO from all other RSNOs (26). The same feature also contributes to the short half-life of the molecule at ambient temperatures, making it more probable that other yet unknown entities are involved as biological mediators of the NO/H 2 S cross-talk.…”
Section: Significancementioning
confidence: 99%
“…However, a key aspect of HSNO's properties that seems to have been overlooked in these discussions is its mobile hydrogen, allowing facile 1,3 hydrogen shift and formation of four isomers with the same chemical equation (13)-a feature described in the seminal studies by Goehring in the 1950s (23) and by Müller and Nonella later on (24,25) that distinguishes HSNO from all other RSNOs (26). The same feature also contributes to the short half-life of the molecule at ambient temperatures, making it more probable that other yet unknown entities are involved as biological mediators of the NO/H 2 S cross-talk.…”
Section: Significancementioning
confidence: 99%
“…14,15 The molecule was produced from photolysis of HNSO, a low-lying stable structural isomer of HSNO (∆H ≥ 10 kcal/mol, 16 see Supplementary Information). Recently, HSNO has been detected under physiologically relevant conditions through protonation of [SNO] − or treatment of S-nitrosoglutathione with sodium sulde by infrared, 15 N NMR and mass spectroscopy. 2 Additionally, coordinated HSNO has been transiently observed by mass spectroscopy 17 and very recently a crystal structure was obtained of an RSNO coordinated to a copper complex.…”
mentioning
confidence: 99%
“…20,24 To explain these paradoxical bonding properties, theoretical models of the electronic structure of RSNOs include contributions from conventional (R−S−N− −O), zwit- In a serendipitous discovery, we found that when a mixture of H 2 S and NO heavily diluted in an inert buer gas (Ne) is expanded into a vacuum chamber, intense rotational lines of a previously unknown molecule, now unambiguously identied as HSNO, are observed by Fourier-transform microwave (FTMW) spectroscopy, a highly sensitive and selective technique which has been used to detect many molecules, both familiar and exotic. 26,27 Rotational transitions ( Figure 1) have been measured for both the cis and trans conformers of the main isotopologue of HSNO and four singly-substituted isotopic species (DSNO, H 34 SNO, HS 15 NO, HSN 18 O). From these data, highly accurate molecular parameters (rotational, centrifugal distortion, and hyperne constants) have been derived (Table S1).…”
mentioning
confidence: 99%
“…The simplest sulfinylimine HNSO, also known as thionylimide, was first prepared by the spontaneous gas phase reaction of ammonia and thionyl chloride at room temperature [2]. Theoretical studies using ab initio molecular orbital and density functional calculations have identified cis-HNSO as the most stable structure on the potential energy surface (PES) and predicted an additional seven structural isomers [3], four of which had already been prepared photolytically from HNSO in a low-temperature matrix and probed by spectroscopic methods [4][5][6][7]. Ultraviolet absorption spectroscopy of HNSO indicated electronic excitation centered at the S atom [8].…”
Section: Introductionmentioning
confidence: 99%